Graphene Nanoplatelets Applied as Functional Fillers in Self-sensing Engineered Cementitious Composites ECC Matrix - Riyadh Ahmed, Shatha; Majeed Al-Dahawi, Ali; Sadeq Hassan, Shatha (Al-Nahrain Journal of Science, 2025)
The widespread adoption of innovative cementitious composites requires proper attention to the controlled performance of structures by using these functional materials. This paper delves deeper into this concept, utilizing a conventional Engineered Cementitious Composites (ECC45) matrix that has been embedded with conductive fillers, enabling it to detect damage in a variety of loading scenarios. As functional fillers, graphene nanoplatelets (GNPs) combined with polyvinyl alcohol (PVA) and nylon (NF) fibers were used at different curing ages of 28, 56, 90, and 180 days. In an attempt to build on previous results and address some knowledge gaps, the simple matrix was incorporated with graphene nanoplatelets at a fixed concentration of 2 % by wt. of cementitious materials along with one of the reinforcement fibers (PVA) or (NF) at 2% volume fraction, which remained constant throughout the experiment. The matrices were tested for compressive strength, splitting strength, three-point flexural strength, and direct tensile strength to evaluate the innovative matrices’ behavior and ability to sense damage under these types of stresses. results demonstrated a unique behavior of the samples due to the excellent behavior of GNPs, particularly during the late curing ages, and the synergistic behavior it exhibits with the reinforcement fibers, which enables entire additives to work in a balanced manner in developing the self-sensing ability in conjunction with the high efficiency of the mechanical properties against the loading conditions described in this paper.